Pengaruh E-Service Quality, Responsivitas Admin Online, dan Kecepatan Layanan terhadap Kepuasan Konsumen L’pitikz Celup Fried Chicken Kec. Dukuhturi Kab.Tegal - Anton Supriyanto; Hendri Sucipto; Nur Khojin; Dumadi Dumadi (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The rapid advancement of digital technology has encouraged culinary businesses to improve service quality to meet evolving consumer needs and expectations. Customer satisfaction has become a key factor in sustaining businesses, particularly those relying on online ordering services. This study aims to analyze the effects of E-Service Quality, Online Admin Responsiveness, and Service Speed on customer satisfaction at L'Pitikz Celup Fried Chicken, Dukuhturi District, Tegal Regency. The research employed a quantitative survey approach. Data were collected through questionnaires distributed to customers who had previously placed online orders, using an accidental sampling technique. The collected data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination with the assistance of SPSS software. The findings reveal that E-Service Quality has a positive and significant effect on customer satisfaction (t = 4.527; p < 0.05). Online Admin Responsiveness has a positive but statistically insignificant effect (t = 1.498; p > 0.05). Meanwhile, Service Speed has a positive and significant influence on customer satisfaction (t = 3.756; p < 0.05). Simultaneously, the three independent variables significantly affect customer satisfaction (F = 40.262; p < 0.05). The study concludes that improving digital service quality and service speed plays a crucial role in enhancing customer satisfaction, while responsiveness of online administrators should continue to be optimized to strengthen service performance.